Analisis Pengaruh Return On Asset (ROA), Return On Equity (ROE) Dan Net Profit Margin (NPM) Terhadap Harga Saham (Studi Pada Perusahaan Perbankan Yang Listed Di Bursa Efek Indonesia Periode 2015-2018) - Yun Fitriano; Meiffa Herfianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study is to determine and empirically prove whether there is an effect of Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) on stock prices. The study population was all banks listed on the Indonesia Stock Exchange (IDX) and the sample was taken using Purpose Sampling as many as 10 banks listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period. The data used is secondary data obtained from the Indonesia Stock Exchange (BEI). The data analysis technique in this study uses multiple linear regression analysis techniques. The results showed that partially there was no significant effect between the variable Return on Assets (ROA) and stock prices as evidenced by a significant value of 0.112> 0.05. For the variable Return on Equity (ROE) has a significant effect on stock prices as evidenced by a significant value of 0.049 <0.05. Meanwhile, the Net Profit Margin (NPM) variable shows the results have a significant effect on the Net Profit Margin (NPM) and the stock price with a significant value of 0.000 <0.05. Simultaneously all Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) variables have a significant effect on stock prices